2013
DOI: 10.1371/journal.pone.0075929
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Antibacterial Effects Are Maintained on Resin-Based TiO2 Nanocomposites after Cessation of UV Irradiation

Abstract: Photocatalysis induced by TiO2 and UV light constitutes a decontamination and antibacterial strategy utilized in many applications including self-cleaning environmental surfaces, water and air treatment. The present work reveals that antibacterial effects induced by photocatalysis can be maintained even after the cessation of UV irradiation. We show that resin-based composites containing 20% TiO2 nanoparticles continue to provide a pronounced antibacterial effect against the pathogens Escherichia coli, Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 35 publications
3
39
1
Order By: Relevance
“…The band gap shift was still towards the visible spectrum, but not to the same degree as the 6% doped Ag-TiO2. This finding was in contrast to other studies, which found the band gap shift continued towards the visible spectrum as the Ag loading of TiO2 continued to increase [14,15]. However, these studies manufactured Ag-TiO2 films using a hybrid sol-gel method, not ball milling, and so the findings cannot be directly compared.…”
Section: Discussioncontrasting
confidence: 62%
“…The band gap shift was still towards the visible spectrum, but not to the same degree as the 6% doped Ag-TiO2. This finding was in contrast to other studies, which found the band gap shift continued towards the visible spectrum as the Ag loading of TiO2 continued to increase [14,15]. However, these studies manufactured Ag-TiO2 films using a hybrid sol-gel method, not ball milling, and so the findings cannot be directly compared.…”
Section: Discussioncontrasting
confidence: 62%
“…In our experiments titania modified samples were continuously exposed to UV light for 10 minutes only.It is well known that bactericidal activity of the samples is closely related to its photocatalytic properties and crystalline structure of synthesized titania [52]. As a result of TiO 2 UV-irradiation reactive oxygen species (OH•, O 2 •, HO 2 •) are generated on its surface.…”
Section: Antibacterial Properties Of Cotton/tio 2 Compositesmentioning
confidence: 99%
“…The photocatalytic antimicrobial effect of a TiO 2 nanocomposite has recently been shown to persist for up to two hours following removal of the UV light source [173]. This may open new avenues for research and application of TiO 2 materials for antimicrobial purposes where application of a constant light source is impractical.…”
Section: ! 30!mentioning
confidence: 97%